An exploration of entrepreneur brand orientation and consumer perceptions of SMEs’ brand positioning - Akintayo Adesoji Ogunsanya; William Edward Heuva; Tshepang Bright Molale (Communicare)
Small business branding is a relatively nascent field of research, and incontrovertible evidence exists that little information on the subject has come from developing regions like Africa. Informed by the knowledge gap, this study explored entrepreneur brand orientation and consumers’ perceptions of their brand positioning. The research was conducted in Mafikeng, North West Province of South Africa. Using qualitative methodology, three entrepreneurs were interviewed and their brand orientation – in terms of understanding and disposition towards branding including positioning strategy they adopt – was explored. Also, two focus group sessions were held with consumers to probe their perceptions of participating SMEs’ brand positioning. As per value for the scholarship, it emerged that the entrepreneurs’ brand orientation was low, resulting in low brand distinctiveness. The focus group sessions corroborated the low brand orientation finding because discussants’ familiarity with and knowledge of the SMEs was almost non-existent, a situation discussants attributed to poor branding and communication. This finding prompted recommendations for entrepreneurs, policymakers and scholarship.